Effects of Magnetic Field and Inclination on Natural Convection in a Cavity Filled with Nanofluids by a Double Multiple-Relaxation-Time Thermal Lattice Boltzmann Method. Issue 3 (4th February 2020) - Zhang, Tao; Che, Defu; Zhu, Yifei; Shi, Hongfei; Chen, Duanyu
Abstract: The present study numerically investigates the magneto-hydrodynamic flow and heat transfer of copper (Cu)-water nanofluids in an inclined cavity with one heat and one cold source. Simulations have been done via double multiple-relaxation-time thermal lattice Boltzmann method. Impacts of Hartmann number, Rayleigh number, inclination angle and the volume fraction of nanoparticles on the fluid flow and heat transfer performance are illustrated in terms of streamlines, isotherms, local, and average Nusselt numbers. Outputs demonstrate that the average Nusselt number decreases remarkably first as the inclination angle increases and then the average Nusselt number increases continuously and approaches a maximum value at a certain inclination angle for high Rayleigh numbers. In addition, the position where the average Nusselt number is maximized moves toward the lower inclination angle with increasing the Hartmann number for high Rayleigh numbers.